Early Ultrastructural Changes in Biopsies From Patients With Symptomatic CKD of Uncertain Etiology - Daniel, Christoph; Enghard, Philipp; Ratnatunga, Neelakanthi; Wijetunge, Sulochana; Wazil, A. W.M.; Zwiener, Christian; Barth, Johannes; Chandrajith, Rohana; Klewer, Monika; Eckardt, Kai-Uwe; Amann, Kerstin Ute; Freund, Paul; et al. (Kidney International Reports, 2023)
Introduction: Although the investigation of chronic kidney disease of uncertain etiology (CKDu) has identified many possible influencing factors in recent years, the exact pathomechanism of this disease remains unclear. Methods: In this study, we collected 13 renal biopsies from patients with symptomatic CKDu (Sym-CKDu) from Sri Lanka with well-documented clinical and socioeconomic factors. We performed light microscopy and electron microscopic evaluation for ultrastructural analysis, which was compared with 100 biopsies from German patients with 20 different kidney diseases. Results: Of the 13 Sri Lankan patients, 12 were men (92.3%), frequently employed in agriculture (50%), and experienced symptoms such as feeling feverish (83.3%), dysuria (83.3%), and arthralgia (66.6%). Light microscopic evaluation using activity and chronicity score revealed that cases represented early stages of CKDu except for 2 biopsies, which showed additional signs of diabetes. Most glomeruli showed only mild changes, such as podocyte foot process effacement on electron microscopy. We found a spectrum of early tubulointerstitial changes including partial loss of brush border in proximal tubules, detachment of tubular cells, enlarged vacuoles, and mitochondrial swelling associated with loss of cristae and dysmorphic lysosomes with electron-dense aggregates. None of these changes occurred exclusively in Sym-CKDu; however, they were significantly more frequent in these cases than in the control cohort. Conclusion: In conclusion, our findings confirm the predominant and early alterations of tubular structure in CKDu that can occur without significant glomerular changes. The ultrastructural changes do not provide concrete evidence of the cause of CKDu but were significantly more frequent in Sym-CKDu than in the controls.
CRIS-Team Scopus Importer:2023-03-17
Keywords: chronic kidney disease of uncertain etiology (CKDu); lysosomal alteration; mitochondrial swelling; renal biopsy; transmission electron microscopy; tubular injury